CLASSIFICATION OF MAIN INDICATORS FOR ASSESSING RELIABILITY AND DIAGNOSTICABILITY OF COMPUTER SYSTEMS - Lipchansky, A. I.; Davydov, A. A. (Radio Electronics, Computer Science, Control, 2024)
In given article is considered the classification of the basic kinds of parameters for a rating of reliability and diagnozability of computer systems. Such parameters were considered: of non-failure operation, of maintainability, of durability, of operational readiness, complex parameters diagnozability. Was given the classification of failures.